Topiramate alters the gut microbiome to aid in its anti-seizure effect - Thai, K'Ehleyr; Taylor, Michael W.; Fernandes, Tatiane; Akinade, Eunice A.; Campbell, Susan L. (Frontiers in Microbiology, 2023)
The role of the gut microbiota in epilepsy has been well studied. However, it remains unclear if anti-seizure medications (ASMs) play a role in the gut-brain axis. To test this, we investigated the impact of the ASM topiramate on the gut microbiome of mice. C57BL/6J mice were administered topiramate in their drinking water for 5 weeks. 16S ribosomal RNA gene sequencing was performed on fecal samples collected at 5 weeks. Analysis of alpha diversity, beta diversity, and differential abundance were performed. Cecal contents were analyzed for short-chain fatty acids (SCFAs) composition. Pentylenetetrazol (PTZ)-kindling was performed in saline, topiramate, Lactobacillus johnsonii, and topiramate and Lactobacillus johnsonii treated mice. Mice received a PTZ injection every other day for a total of twelve injections, seizure activity was video monitored for 30 minutes and scored. Our study showed that topiramate ingestion significantly increased Lactobacillus johnsonii in the gut microbiome of naïve mice. Treatment with topiramate and Lactobacillus johnsonii together, but not alone, reduced susceptibility to PTZ-induced seizures. Co-treatment also 2 This is a provisional file, not the final typeset article significantly increased the percent of butyrate and the abundance of butyrate-producing family Lachnospiraceae in the gut and elevated the GABA/glutamate ratio in the cortex. Our results demonstrate that an ASM can alter the gut microbiome to aid in their anti-seizure effect in vivo. Our results suggest the potential of Lactobacillus johnsonii as an adjunct therapy with topiramate in reducing seizure susceptibility.